Cistanche deserticola-derived exosome-like nanovesicles target the Microbiota-GABA signaling axis to ameliorate loperamide-induced constipation - Zhang, Xiaoyu; Yan, Keqiu; Bao, Xinkun; Yang, Dequn; Chen, Xiaoyin; Xiao, Wenjie; Zhou, Jinbo; Cai, Yifan; Wang, Hao; Sun, Guangjun; Lin, Aizhen (Frontiers in Pharmacology, 2025)
IntroductionConstipation is a prevalent gastrointestinal disorder with limited therapeutic options that often lead to laxative dependence. Gut microbiota and their metabolic regulation represent promising therapeutic targets.MethodsIn this study, we isolated and characterized exosome-like nanovesicles from the traditional Chinese herb Cistanche deserticola (CELNs) and evaluated their efficacy in a loperamide-induced mouse model of constipation.ResultsWe found that CELNs administration significantly alleviated constipation phenotypes, as evidenced by increased fecal output, water content, and intestinal transit rate, alongside the restoration of colonic histology and goblet cell function. Multiomic analyses revealed that CELNs remodeled the gut microbiota by enriching GABA-producing genera, such as Lactobacillus and Bacteroides, consequently elevating intestinal GABA levels. This increased GABA specifically activated GABAA receptor subunits α2 and β2/3, thereby enhancing intestinal smooth muscle contraction. Crucially, the therapeutic effects of CELNs were entirely abolished by a GABAA R antagonist, confirming that their action is dependent on GABAA R signaling activation.DiscussionIn summary, our study reveals a novel mechanism through which CELNs enhance intestinal motility via the microbiota–metabolite–host axis, offering a conceptual foundation and a potential nanotherapeutic strategy for the targeted treatment of constipation by modulating microbial homeostasis.